The Pengaruh Current Ratio Dan Return On Equity Terhadap Return Saham (Studi Kasus Pada Perusahaan Pertambangan Di Bursa Efek Indonesiaperiode 2017-2021) - Agustinus Deyafajar Jiwantono; Nunung Nurhasanah; Sri Suartini (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Stock returns in mining companies are the results of profits obtained by investors from stock investments made. So that steps to save investors' investment it is necessary to carry out fundamental analysis. One of these analyzes is financial ratios such as the current ratio and return on equity. The purpose of this study is to analyze whether the CR and ROE variables have a partial and simultaneous effect on stock returns. The population used is all mining companies listed on the Indonesia Stock Exchange in 2017-2021 with a sample of 10 companies. This research is quantitative with purposive sampling technique. The data used in the form of financial statements that have been published by the IDX and then processed using SPSS 18. The data is processed using multiple linear regression analysis models. Meanwhile, the hypothesis test was carried out using the T test and F test. The results of this study indicate that partially CR has no significant effect on stock returns, while ROE has a negative effect on stock returns. Meanwhile, simultaneously CR and ROE have a joint effect on stock returns of 19.10%, while the remaining 80.90% is explained by other variables outside the research model. Keywords: current ratio, return on equity, stock return